DECLINE IN PROFITS DURING THE COVID-19 PANDEMIC ON EXPEDITION OF PT. KARYA MAKMUR MEDAN - Rizkina, Miftha; Junawan, Junawan (International Proceeding of Law and Economic, 2020)
The purpose of this research is to see a decrease in profit on the expedition of PT. Karya Makmur during the Covid 19 pandemic. This can be seen from the lack of availability of goods in the warehouse, the large number of trucks / night queues, and also the limitation of the collection of groceries by suppliers from Medan so that this can result in a decrease in profits on the expedition of PT. Karya Makmur. The research method used is descriptive method with a qualitative approach.